Effects of Fusaric Acid in Broiler Chicks and Turkey Poults - Ogunbo, S.O.; Ledoux, D.R.; Broomhead, J.N.; Bermudez, A.J.; Rottinghaus, G.E. (International Journal of Poultry Science, 2005)
Two experiments were conducted to evaluate the effects of fusaric acid (FA) in broiler chicks (Exp. 1) and turkey poults (Exp. 2). In each experiment, 100 day-old birds were allotted randomly to dietary treatments containing 0, 100, 200, 300, or 400 mg FA/kg of feed. Each dietary treatment was fed to 4 pen replicates of 5 birds each for 21 days. Fusaric acid had no effect (P > 0.05) on feed intake, body weight gain, or feed conversion, which averaged 864 g, 627 g, and 1.38 g/g, and 656 g, 496 g and 1.33 g/g for chicks and poults, respectively. There were no treatment effects on organ weights of poults, however, chicks fed FA had lower (P < 0.05) kidney weights compared to controls. There were no treatment effects on hematology of chicks, however, poults fed the highest level of FA had (P < 0.05) higher hemoglobin and mean cell hemoglobin levels compared to chicks fed 100 mg FA/kg diet. Brain frontal cortex concentrations of norepinephrine, epinephrine, dopamine, and serotonin in poults were not affected by treatment (P > 0.05), but chicks fed 100, 200 and 300 mg FA/kg diet had higher brain concentrations of norepinephrine (P < 0.05) compared to controls. Chicks fed 300 and 400 mg FA/kg also had higher concentrations of epinephrine (P < 0.05) compared to controls. Results indicate that FA is not toxic to broiler chicks or turkey poults at these dietary concentrations.